Coordination of elicitors and ascorbate-glutathione cycle: A vital nexus for mitigating post-harvest injury and losses of cultivated fruits - Md. Injamum-Ul- Hoque; Md. Entaduzzaman Jony; Ashim Kumar Das; Shifa Shaffique; Md.Mezanur Rahman; Imdadul Haque Sharif; S.M. Ahsan (Plant Trends, 2024)
Fruit losses and waste are predominantly caused by postharvest diseases, with their management traditionally reliant on pesticides. The extensive utilisation of synthetic fungicides can cause harmful impacts on both human health and the environment, necessitating a reduction in their use. Recent advancements have led to the development of novel, benign strategies using natural or biologically derived compounds. These compounds, known as 'elicitors,' have the strength to instigate the plant's defence mechanism, enhancing the fruit's resilience counter to future stress and reducing postharvest spoilage. In recent years, the impact of the plant defence system concerning elicitor compounds has been measurable through physiological parameters or the enzymatic activity of molecular markers. Antioxidant activity, a crucial parameter to determine fruit quality and tolerance to biotic and abiotic stresses, significantly functions in stress response and maintaining postharvest quality. Elicitors can prompt endurance in fruits instead of diverse environmental stresses by promoting the biosynthesis of antioxidant components and enhancing antioxidant capability through the ascorbate-glutathione (AsA-GSH) cycle. Recent findings have exhibited that applying chemical elicitors can enhance antioxidant activity by augmenting the content of AsA and GSH and by regulating the redox stability, thereby maintaining quality in harvested fruits. This review summarises recent findings demonstrating how elicitor sprays enrich antioxidant activity in harvested fruits by accelerating the synthesis of antioxidants and defence components. This provides insight into fruit defence mechanisms induced under various elicitors and their prospects in postharvest biology. [Plant Trends 2024; 2(2.000): 24-37]